Applying fuzzy logic to software usability evaluation - Guchenko, I. V. (Problems of Informatization and Control, 2013)
Article is devoted to the issue of modification of earlier developed usability evaluation model withfuzzy multi-criteria weighted average approach. Usability is represented as a four-level hierarchicalsystem of usability criteria. Usability subcharacteristics from ISO/IEC 25010:2011 were taken. Modelsupports usability management of software products based on the experts’ judgments and evaluationof users’ feedback. Fuzzy logic is applied to deal with the uncertainty and imprecision of the importanceand rating of criteria on which usability depends.